Paper parade - Weeks, Sarah (Atheneum Books for Young Readers, 2004)
A young girl watches a parade from her bedroom window, then falls asleep and dreams that she has joined the procession. Annotation. A little girl wants to go to the parade SOOOO very badly. Her baby brother is in need of his nap, nap, nap. What's a girl to do? Create her own parade, of course.... starring: Ba-rum-pum-pum!